Caracterización Morfométrica de la población equina en la caballeria de sangre N° 7 Cazadores de los Rios Loja, Ecuador - Chiriboga Calva, Angela Carolina (2017)
The aim of this work was to characterize the body morphology in the equine population of the Caballería de Sangre Nº 7 “Cazadores de los Rios”. Through which, we did the morphological characterization of 18 equines, group consisting of 8 mares and 10 males,with ages ranging between 5 months and 19 years, through which we studied their measurements and zoometric indexes, measurements taken with a long zoommetal stick, drill compass, gauge and tape measure, and indexes resulting from predetermined formulas, these data were analyzed using the statistical package SAS version 9.0. We don’t found no significant differences between sexes; while comparing animals least than one year and more than four years of age, we found differences (P <0.01) in all variables. For this reason to characterize the Horse of the Caballería Nº 7 we focus on the animals older than four years since in these the measures have reached their maximum development, obtaining the following average values ​​of the measurements zoométricas of the head: for the width of ears, Length of ears, head width and head length of 5.06; 17.2; 22.2 and 58.8 cm respectively, and for the body for the variables raised to the cross, raised to the rump, dorso-sternal raised, body length, croup length, bi-costal width, width of anterior croup , Width of the posterior croup, thoracic perimeter and perimeter of the anterior cane, the measures found are 149; 149; 65.5; 147; 48.8; 35.0; 51.8; 29.1; 175; And 21.0 cm, the mean values ​​of the indices were obtained: 38.2 head index, 84.2 body index, 53.9 thoracic index, 43.9 relative depth index Breast, 107 pelvic index, 11.9 metacarpal index, 101 proportionality index; classified according to the indexes in dolichocephalous, breviary, mesothoracic, mesomorphic, dolicopelvic, eumetric, means, while the estimated weight was 380 kg, in this way it was determined that the horse studied for its zoometric characteristics shows aptitude for sports activities. Key words: Measurements, indexes, aptitude, sport.